KARAKTERISTIK PENDERITA INFEKSI MENULAR SEKSUAL DI WILAYAH KERJA PUSKESMAS BANDAR BARU TAHUN 2013 - Sylvana Dyna Theresia; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT STIs is a public health problem that is quite prevalent in some parts of the world. It is estimated that more than 340 million cases of STIs occur each year. To determine the characteristics of patients with STIs at Bandar Baru Public Health Center in 2013. This research conducted a descriptive study with case series design. Location is in Bandar Baru Public Health Center. Population and sample the data amount to 155 STI patients. Collecting data using secondary data. Univariate data were analyzed descriptively and bivariate data were analyzed with Chi-square. From the recorded data, obtained results the highest proportion aged 25-29 years (31.6%) with the youngest aged 18 and the eldest 62 years old, female (78.1%), education level is moderate (79.4%), married (34.2%), District Sibolangit (52.95), female from District Sibolangit (80,5%), the first visit (85.2%), the last time having sex ≤ 2 days (78.7%), sexual partner in the week ≤ 5 people (58.7%), the type of IMS suffered IGNS (55.5%). From analysis of data obtained, the proportion of patients with marital status were significantly different (78,1% vs 21%; X2=26,908; p=0.001), the proportion of patients with the last time having sex ≤ 2 days was significantly different (78.7% vs. 21.3%, X2=18.616, p= 0.000), and the proportion of patients with a sexual partner in a week ≤ 5 were significantly different (58.7% vs. 41.3%, X2=6.058, p=0.014). Bandar Baru Public Health Center expected to increase dissemination of the importance went to the STI clinics; improve preventive and promotive programs for the prevention of STIs; run distribution of free condoms regularly; cooperation with stakeholders and NGOs; doing some efforts to close a prostitution location in Bandar Baru; complete recording data of STI patients, especially regarding the type of work. Keywords: STIs, Patients Characteristics